Intervensi Menghilangkan Stigma dan Diskriminasi Kusta di Puskesmas Pauh Kamba, Padang Pariaman - Tutty Ariani; Rina Gustia; Satya Wydya Yenny; Qaira Anum; Gardenia Akhyar; Ennesta Asri; Irdawati Izrul; Yenni Raflis; Rizkia Chairani Asri; Mardhiati Mardhiati; Riri Prima Yolanda (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2022)
The increase in new leprosy cases in the year 2021 spread across 19 regencies, with the highest distribution in Padang Pariaman, and it is still a problem in West Sumatera Province. Based on this condition,